1-Year Post-loading of Short and Ultrashort Implants in Posterior Mandibular and Maxillary Regions - ElAdl, Noha M.; Sholkamy, Hisham M.; Emara, Aala'a S. (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Short implants have been proposed as an option for management of deficient alveolar ridges without the need for complex augmentation procedures. AIM: In this study, we aim to assess the use of short and ultrashort implants for the management of deficient alveolar ridges in posterior mandibular and maxillary areas with a 1-year post-loading follow-up. METHODOLOGY: Ten patients were recruited in this trial with a total of 14 implants to be placed. The patients all needed implants in the maxillary/mandibular posterior regions for prosthetic rehabilitation with deficient alveolar ridge heights. Implants of 5 mm diameter and lengths either 6 or 8.5 mm were to be placed in the edentulous spaces after proper radiographic assessment. Two-stage surgeries were followed with ¾ months between implant placement and loading. The follow-up lasted for a year to allow for peri-implant clinical assessment and radiographic analysis. RESULTS: All patients showed uneventful healing and no infection, wound dehiscence or inflammation was noted. Prosthetic rehabilitation was successful and satisfactory to the patients. None of the cases showed excessive marginal bone loss and stability was maintained at acceptable levels to the end of the follow-up period. CONCLUSION: Within the limitations of this study, short and ultrashort implants seem like a valid option for management of posterior edentulous regions with deficient ridge heights.